Legal regulation of real estate appraisal services - Andreevna Neznamova, Alla; Aleksandrovna Volkova, Maria; Sergeevna Smaginа, Olga; Vladimirovna Efimova, Olga (Opción, 2019)
The aim of the article is to research the issues of civil law regulation of real estate appraisal services. The need to assess market, cadastral or other values is the cause of appraisal valuations’ paramount importance for physi- cal and legal entities. The increased concern in appraisal services may be determined by either legislative requirements or proactive initiatives aimed to protect ownership interests in purchase and sale bargains, in equitable property division, share allocation, property exchange, property donation, redemption of government or municipal property; rent registration; entering into inheritance; mortgage registration; assessment of real estate market value for tax administration, etc.